1981
DOI: 10.1111/j.1469-8137.1981.tb02320.x
|View full text |Cite
|
Sign up to set email alerts
|

Domains of Atpase in Plasma Membranes and Transport Through Infected Plant Cells

Abstract: Summary The sites of ATPase at pH 7·2 and β‐glycerophosphatase at pH 5·5 and 7·2 in the presence of Mg2+ have been determined by a lead precipitation technique and electron microscopy in leaves of Pisum sativum and Phaseolus vulgaris infected, respectively, with Erysiphe pisi and Uromyces appendiculatus. In the two plants, ATPase activity was similarly high in plasma membranes of epidermal, phloem transfer and companion cells and much lower in those of their mesophylls. The domain of the host plasma membrane i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 17 publications
3
28
1
Order By: Relevance
“…Previous ultrastructural studies with the lead/phosphate precipitation technique did not detect ATPase activity in the haustorial plasma membrane of Uromyces appendiculatus but in the plasma membrane of Erysiphe pisi haustoria (Spencer-Phillips and Gay, 1981). This cytochemical technique, however, has been critized as being not specific for the H + -ATPase (Katz et al, 1988).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous ultrastructural studies with the lead/phosphate precipitation technique did not detect ATPase activity in the haustorial plasma membrane of Uromyces appendiculatus but in the plasma membrane of Erysiphe pisi haustoria (Spencer-Phillips and Gay, 1981). This cytochemical technique, however, has been critized as being not specific for the H + -ATPase (Katz et al, 1988).…”
Section: Discussionmentioning
confidence: 93%
“…Active transport of nutrients across the host-haustorial interface has been suggested. This was founded on ultrastructural localization of ATPase activity in the fungal plasma membrane (Spencer-Phillips and Gay, 1981;Woods and Gay, 1987). The plasma membrane H + -ATPase of fungi and plants generates the electrochemical proton gradient which is essential for active transport of solutes into cells.…”
mentioning
confidence: 99%
“…Low apoplastic concentrations could be one explanation for the evolution of haustoria if they form an interface at which increased metabolite efflux from the host cell occurs, due to an increase in cytoplasmic solute concentration or plasma membrane permeability (Patrick 1989). Evidence for the latter has been obtained by cytochemical studies that indicate that the host-derived extrahaustorial membrane might be depolarized due to the lack of plasma membrane ATPase activity (Spencer-Phillips and Gay 1981;Baka et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis was founded on cytochemical investigations of plants infected by powdery mildew and rust fungi (Spencer-Phillips & Gay, 1981). It was found that the region of the host plasma membrane invaginated around each haustorium did not exhibit the ATPase activity characteristic of the rest of the plasma membrane, which was indistinguishable from that in uninfected tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the host cells are not killed, they sustain abnormal losses. An hypothesis for its operation in infections by fungal haustoria was first proposed by Spencer-Phillips & Gay (1981) and has subsequently been applied to a wide range of species of pathogens and plants. However, it has not been confirmed by dynamic experiments and the present paper seeks to remedy the deficiency.…”
Section: Introductionmentioning
confidence: 99%